2017
DOI: 10.2134/agronj2016.07.0401
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Yield, Starch, and Protein of Dry Pea Grown Across Montana

Abstract: Core Ideas Dry pea yield, protein, and resistant starch varied greatly across Montana. Yield and protein were mainly determined by environments. Resistant starch is controlled by genetics to a great extent. Effects of drought index, growth period, seed size, and seed weight on yield, protein, and starch were analyzed. Pea (Pisum sativum L.) has long been an important component of the human diet, providing an excellent source of protein. In addition to its protein, pea starch, especially resistant starch (RS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
(26 reference statements)
5
23
0
Order By: Relevance
“…Our results are similar to those reported by several authors [30,41] and it is in the global average of 29% mentioned by [44]. Compared with other pulses, such as pea, which have CP contents from 15 to 30% dry weight [45], it was found that Vicia faba var minor have acceptable levels [46]. On the other hand, compared to forages such as barley and straw which have low CP levels from 6 to 10 %, faba bean have the advantage of providing a ration richer in CP, it can therefore be associated with these poor forages in nitrogen to relatively improve CP level in animal feed [47,48].…”
Section: Chemical Composition and Nutritivesupporting
confidence: 92%
“…Our results are similar to those reported by several authors [30,41] and it is in the global average of 29% mentioned by [44]. Compared with other pulses, such as pea, which have CP contents from 15 to 30% dry weight [45], it was found that Vicia faba var minor have acceptable levels [46]. On the other hand, compared to forages such as barley and straw which have low CP levels from 6 to 10 %, faba bean have the advantage of providing a ration richer in CP, it can therefore be associated with these poor forages in nitrogen to relatively improve CP level in animal feed [47,48].…”
Section: Chemical Composition and Nutritivesupporting
confidence: 92%
“…Similarly, Tao et al. (2017) and Mohammed et al. (2018) reported protein contents of 15.9%–25.1% and 14.5%–27.8%, respectively.…”
Section: Protein Content Is Affected By Genetic and Environmental Factorsmentioning
confidence: 80%
“…However, it has been found that increasing protein intake at all stages of life may reduce muscle decline and its associated health conditions ( Stevenson et al, 2018 ). Protein makes up around 15–30% of dry pea seeds, more typically 20–28% in cultivars ( Burstin et al, 2007 ; PGRO, 2020 ), with this fraction mainly comprised of globulin and albumin storage proteins ( Tao et al, 2017 ; Tömösközi et al, 2001 ; Tzitzikas et al, 2006 ). Pea seed protein composition is complex genetically, with multigene families encoding different proteins, which are then subject to considerable post-translational processing ( Bourgeois et al, 2011 ).…”
Section: Proteinmentioning
confidence: 99%